1991
DOI: 10.1016/s0022-5347(17)38261-7
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Triplication and Ureterocele: Report of 3 Cases and Review of the Literature

Abstract: We report 3 cases of ureterocele associated with ureteral triplication and review the literature. Ureteral triplication was type I in 2 patients and type II in 1. Diagnosis was established preoperatively in 2 cases and intraoperatively in 1. All patients were initially treated by upper pole partial nephrectomy and aspiration of the ureterocele, leaving the ureteral stump open in the retroperitoneum. Subsequent excision of the ureterocele and ureteral reimplantation for persistent ipsilateral vesicoureteral ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Finkel and Gosalbez reported ureteroceles associated with type I and rarely with type II ureteral triplications [3,4]. In recent review of the literature, Pode [7] and Merlini [6] reported ureteral triplication cases associated with obstruction; however, in the case reported by Merlini et al obstruction was caused by ureteroureteric reflux, while the other one was due to uretero-vesical stenosis [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finkel and Gosalbez reported ureteroceles associated with type I and rarely with type II ureteral triplications [3,4]. In recent review of the literature, Pode [7] and Merlini [6] reported ureteral triplication cases associated with obstruction; however, in the case reported by Merlini et al obstruction was caused by ureteroureteric reflux, while the other one was due to uretero-vesical stenosis [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Ureteral triplication is a rare congenital anomaly of the ureter [1,2,[4][5][6][7][8][9]. It is a developmental abnormality of the ureteral bud originating from the Wolffian duct at the 50 week of embryological life [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triplication may remain asymptomatic (8% of cases) or present with recurrent UTIs, urinary incontinence or renal colic. In triplication with associated persistent UTIs, heminephrectomy with removal of the supernumerary ureters has been shown to be effective [6]. Although ureteroureterostomy may be beneficial, when incontinence has been the presenting complaint, the ectopic ureter should be removed [7].…”
Section: Discussionmentioning
confidence: 99%
“…The most common presenting symptoms in ureteral triplication are renal colic, recurrent urinary tract infection and urinary incontinence [2,3] . Other urological anomalies commonly associated with ureteral triplication include contralateral duplications, ureteral ectopia, renal dysplasia, vesicoureteral reflux and pelvis ureterostenoma [4][5][6] .We report the diagnosis and treatment of a case of right ureteral triplication combined with renal ectopia and ureteral cyst. To our knowledge, such a ureteral malformation has not been described previously.…”
mentioning
confidence: 98%